The CARD Act and Young Borrowers: The Effects and the Affected. Issue 7 (15th September 2016) - DEBBAUT, PETER; GHENT, ANDRA; KUDLYAK, MARIANNA
Abstract : We study a new law that restricts credit to individuals under age 21. We first use a difference‐in‐difference approach to estimate the effect of the law on credit card availability. Following the passage of the law, individuals under age 21 are 8 percentage points (15%) less likely to have a credit card, have fewer cards, and, conditional on having a card at all, are 35% more likely to have a cosigned card. We then use data from before the passage of the law to identify the characteristics of those individuals most likely to be affected by the Act.